The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/spe.2935
|View full text |Cite
|
Sign up to set email alerts
|

Multiuser collaborative illustration and visualization for volumetric scientific data

Abstract: Multiuser can collaboratively complete complex visualization tasks that cannot be completed by a single user. Although multiuser collaboration system has made great progress, there are many challenges in the collaborative visualization of 3D volumetric scientific data due to the difficulties in multiuser collaboration, and collaborative slice analysis. This article proposes a client‐server based collaborative visualization system, which consists of a 3D volume explorer and a 2D slice analyzer, to help domain e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Transfer function, which is an interactive analysis method, enables users to select RGBA values of different hardness values, so as to obtain the final interpretation effect [10]. According to the terms of dimensionality, we can easily classify data-centric transfer functions into one-dimensional, two-dimensional, and higher-dimensional forms.…”
Section: Data-centric Transfer Functionsmentioning
confidence: 99%
“…Transfer function, which is an interactive analysis method, enables users to select RGBA values of different hardness values, so as to obtain the final interpretation effect [10]. According to the terms of dimensionality, we can easily classify data-centric transfer functions into one-dimensional, two-dimensional, and higher-dimensional forms.…”
Section: Data-centric Transfer Functionsmentioning
confidence: 99%
“…In the learning situations, the teacher usually explains the phenomena or operation, and other participants will be observing a demonstration, but a true collaboration with active participants can also be arranged. Luxenburger et al [23] demonstrated a system where the participants studied shared electronic patient records in VR and Liu et al [24] had a collaborative VR system where several domain experts can study the same medical data. Butnaru and Girbacia [25] explored collaborative bone surgery planning in a tele-immersive environment with networked Cave Automatic Virtual Environment (CAVE) systems and other stereoscopic desktop displays.…”
Section: Introductionmentioning
confidence: 99%
“…Recent decades have seen a growing interest and demand for human-centered collaborative systems, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] which allow people to work together and achieve the same goals over computer networks. One of the most popular human-centered collaborative systems is real-time collaborative editors (co-editors).…”
Section: Introductionmentioning
confidence: 99%